The Effect of Athletic Mental Energy on Sports Mental Training and Sports Courage in Rugby Players - Ahmet İslam (Journal of Educational Issues, 2024)
This study aimed to determine whether athletic mental energy played a mediating role between sports mental training and sports courage in rugby players. The study developed an original theoretical model, which was tested using the Sobel test. The sample consisted of 309 rugby players in the 15 men’s, 7’s women-men, U18 7’s men’s-women’s rugby leagues of the 2021-2022 Turkish Rugby Federation. The sample consisted of rugby players aged 18 to 35 years of age. Data were collected using a sociodemographic characteristics questionnaire, the Sports Mental Training Questionnaire (SMTQ), the Sports Courage Scale-31 (SCS-31), and the Athletic Mental Energy Scale (AMES). There was a positive correlation between mental training and athletic mental energy. There was a positive correlation between athletic mental energy and sports courage. There was a positive correlation between mental training and sports courage. Moreover, athletic mental energy played a fully mediating role between sports courage and mental training. The results confirmed the theoretical model. These results will pave the way for further research and contribute to the literature as they are a reflection of the cycle in the model. Authorities should inform rugby players about the relationship between athletic mental energy, mental training, and sports courage.